PENGARUH METODE BERMAIN PLIOMETRIK TERHADAP HASIL BELAJAR LOMPAT JAUH PESERTA DIDIK SMP NEGERI 7 SUNGAI RAYA - Setiadi, Wahyu; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to know the influence of pliometric playing method on the learning result of long jump on the students of class VIII SMP Negeri 7 Sungai Raya. The population in this study were 134 students with a sample of 68 students who then divided into two groups, namely 34 students in the experimental group and 34 students in the control group. Technique of writing data in this research is pretest, treatmen and posttest. The data recording device in this study is a long jump test. The conclusion of this research is, after doing research and doing analysis which can be concluded that the result is better than the participant who is the average of student. The average value of the group before the initial measurement was 2.16 meters and after the interview using the measurement method from the end of 2.44 meters the mean average in the experimental group was 0.28 meters. While the value-in control group on the test was 2.18 meters and increased by 2.28 meters in the mean group by 0.1 meters.Keywords: Pliometric, Learning Outcomes, Long Jump